PENERAPAN MODEL LEARNING START WITH A QUESTION MENGGUNAKAN GAMBAR UNTUK MENINGKATKAN PEMAHAMAN SISWA KELAS V PADA MATERI IPAS - Butar - Butar, Elianora; Nurjannah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine the effect of implementing the Learning Start With a Question (LSQ) model using images on improving the understanding of fifth grade students in the Natural and Social Sciences (IPAS) subject. This study uses a quantitative approach with a quasi-experimental design involving two classes, namely the experimental class (using the LSQ model with images) and the control class (using regular learning). Data collection techniques were carried out through pretest and posttest tests, as well as instrument validity and reliability tests. The results showed that the average posttest score of students in the experimental class was higher than that of the control class. The results of the t-test showed a significance value of 0.000 <0.05, which means that there is a significant effect of implementing the LSQ model using images on student understanding. Thus, it can be concluded that the LSQ model with the help of image media is effective in improving students' understanding of the IPAS material.